2009
DOI: 10.1002/jcb.22336
|View full text |Cite
|
Sign up to set email alerts
|

SUMF2 interacts with interleukin‐13 and inhibits interleukin‐13 secretion in bronchial smooth muscle cells

Abstract: IL-13 is a central mediator of allergic inflammation and secreted by Th2 and bronchial smooth muscle cells (BSMC). However, little is known about the regulation of IL-13 secretion. To address it, a cDNA library of BSMC was screened for the proteins interacted with IL-13 by yeast two-hybridization. Besides IL-13 receptors, human sulfatase modifying factor 2 (SUMF2) was interacted with IL-13. Furthermore, SUMF2 and IL-13 were co-immunoprecipitated from BSMC, which was independent of IL-13 glycosylation. Interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Production of IL-13 and infiltration of IL-13-postive cells in the submucosal region of the airway has been associated with AHR (34,35). In addition to T H 2 lymphocytes, IL-13 is secreted by many cell types in the asthmatic airway, including macrophages (36), mast cells (37), airway smooth muscle cells (38), and airway epithelial cells (39). Our histologic examination of endobronchial biopsy airway tissue sections from these patients indicated the presence of inflammatory cells that may be capable of producing IL-13 and stimulating airway fibroblast invasion.…”
Section: Discussionmentioning
confidence: 91%
“…Production of IL-13 and infiltration of IL-13-postive cells in the submucosal region of the airway has been associated with AHR (34,35). In addition to T H 2 lymphocytes, IL-13 is secreted by many cell types in the asthmatic airway, including macrophages (36), mast cells (37), airway smooth muscle cells (38), and airway epithelial cells (39). Our histologic examination of endobronchial biopsy airway tissue sections from these patients indicated the presence of inflammatory cells that may be capable of producing IL-13 and stimulating airway fibroblast invasion.…”
Section: Discussionmentioning
confidence: 91%
“…At deep RNASeq in GENE study samples, expression of sulfatase modifying factor 2 (SUMF2) was regulated by LPS in blood and PBMCs and was identified in the eQTL analysis in multiple tissues. SUMF2 interacts with interleukin-13 (IL-13), a cytokine associated with allergic inflammation, and its expression in lymphocytes was shown to inhibit secretion of IL-13 (34). IL-13 promotes activation of alternative M2 monocyte/macrophages, thereby inhibiting pro-inflammatory cytokines and chemokines (35).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have shown that in addition to interacting with IL-13 receptors, SUMF2 interacts with IL-13. Furthermore, SUMF2 inhibits the secretion of IL-13 independently of IL-13 glycosylation (Liang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…When we induced transient SUMF2 expression in lymphocytes, we found that amounts of the 12-kDa form of intracellular IL-13 were significantly increased, whereas levels of IL-13 in lymphocyte culture supernatants were significantly reduced. In addition, blocking N-glycosylation via treatment with tunicamycin eliminated the 17-kDa form of intracellular IL-13 but failed to promote the secretion of IL-13 by bronchial smooth muscle cells (Liang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%